Temporally Mapping Ease of Walkability in Boston Chinatown - Duong, Tony. (Tufts University. Tisch Library., 2024)
Thesis (M.A.)--Tufts University, 2024.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Justin Hollander.; Committee: Christine Cousineau.; Keywords: Urban planning, Area planning & development, and Civil engineering.